A luminescent Zn(II) coordination polymer for selective metal ions detection and treatment activity on tuberculosis by inhibiting the ropA gene expression in Mycobacterium. (23rd February 2022) - Tang, Jun; Qian, Ling; Wu, Bei-Shou; Liang, Qiu
ABSTRACT: By utilising the mixed-ligand approach, a novel coordination polymer based on Zn(II) ions as nodes have been synthesised by the Zn(NO3 )2  · 6H2 O reacting with 1, 4-H2 NDC in the presence of a second N-donor ligand L, and its chemical formula is {[Zn(L)1.5 (1, 4-NDC)]·H2 O} n (1, 1, 4-H2 NDC = 1, 4-naphthalenedicarboxylic acid and L =  N, N′ -di(4-pyridyl)suberoamide). The as-synthesised complex 1 reveals outstanding water stability and it could be utilised as a platform of the multi-responsive recyclable luminescent sensor for the Al 3+ and Fe 3+ in water. The compound was synthesised in this research for the tuberculosis treatment. The biological function of the compound was assessed, and its detailed mechanism was explored. The Mycobacterium bacterial numbers in lung tissue was determined with spread plate method. In addition to this, the real-time reverse transcription-polymerase chain reaction (RT-PCR) method was conducted to determine the inhibition of compound against the ropA expression in Mycobacterium .